Maximizing versus satisficing: Negative correlation between maximizing attitude and school domain satisfaction - Beja, Edsel L, Jr (Archīum Ateneo, 2019)
The study uses a projection method to identify maximizing and satisficing individuals in a sample of college students from the Philippines. The study defines a maximizing individual as one who sketches a full glass that is filled up to the brim and a satisficing individual as one who sketches a full glass that is filled below the brim. The study also uses data on school domain satisfaction of the college students. The analysis finds that individuals who maximize also experience lower school domain satisfaction.